Ethanol Extract, Ethyl Acetate Extract, Ethyl Acetate Fraction, and n-Heksan Fraction Mangosteen Peels (Garcinia mangostana L.) As Source of Bioactive Substance Free-Radical Scavengers - Liza Pratiwi; Achmad Fudholi; Ronny Martien; Suwidjiyo Pramono (JPSCR: Journal of Pharmaceutical Science and Clinical Research, 2016)
Mangosteen peels (Garcinia mangostana L.) is well known as an excellent source of antioxidative compounds. The name of mangosteen is xanthone. Antioxidant of mangosteen  peels can be extracted by ethanol, etyl acetate and can be fractinated by etyl acetate and n-hexane. The aim of this research was to compare the antioxidant activity of the peel extract by ethanol and etyl acetate and fractinated by etyl acetate and n-hexane. Extract and fraction exhibited higher scavenging activity of DPPH. The purpose of this study was to compare antioxidant activity of ethanol extract, ethyl acetate extract, fraction of ethyl acetate and n-hexane fraction. The antioxidant activity test using DPPH method with UV-Vis spectrophotometer. Ethanol extract shown IC50 value 5,03 µg/mL, ethyl acetate extract shown IC50 value 41,56 µg/mL. Ethyl acetate fraction shown IC50 value 2,78 µg/mL, and n-hexane fraction with IC50 22,33 µg/mL. It means peel extract and fraction by mangosteen peels has very strong antioxidant activity and ethyl acetate fraction that its antioxidant activity higher that the other solvent.